ANALYSIS THROUGH THE IMPLEMENTATION OF REGIONAL PROPERTY MANAGEMENT POLICY IN AN EFFORT TO ACCOMPLISHED GOOD GOVERNANCE AT LOCAL FINANCIAL AND ASSETS MANAGEMENT OFFICE (BPKAD) IN TANGERANG SELATAN CITY - Sundari, Sri; Sri Lestariningsih, Wahyuni (Dinasti International Journal of Digital Business Management, 2021)
This research aims to investigate and evaluate the implementation of regional property management policies at the Local Financial and Assets Management Office (BPKAD) in Tangerang Selatan City. It was trying to find out the factors which hinder the implementation of regional property management policies, analyze about the obstacles which are faced in improving good governance and analyze the strategies undertaken in the implementation of regional property management policies in order to realize good governance. This research currently uses a descriptive qualitative method with the insider respondents from BPKAD office in Tangerang Selatan City. The collection of data techniques has been done through observation and interviews. The theory from George C Edward III has been used as a reference which stated that there are four things that will affect the implementation of policies, namely communication, resources, disposition and bureaucratic structure. According to the research findings, it is known that the implementation of regional property management policies in Tangerang Selatan City's BPKAD has been going well, but there are still few regulations which have not been fully accomplished. The factors which support the implementation of regional property management policies in Tangerang Selatan City's BPKAD are communication, disposition, bureaucratic structure, resources. Meanwhile, the factors which hinder its implementation are Bureaucratic structure, resources, disposition. In order to overcome these obstacles, the efforts that have been made namely; immediately apply the concept of institutional strengthening, more focus on improving the governance of regional property so that good governance could be realized and strengthened in terms of regulation and preparation from Standard Operating Procedures in the management of property area.